The impact of dimethylaminohexadecyl methacrylates on the physical and antibacterial properties of endodontic sealers - Faisal Alharamlah; Fawaz AlTuwaijri; Haitham AlQuorain; Abdul Samad Khan; Faisal Alonaizan; Rashed Alsahafi; Michael D. Weir; Hockin H. K. Xu; Abdulrahman A. Balhaddad (Frontiers in Oral Health)
ObjectiveThis study aims to incorporate contact-killing quaternary ammonium into two root canal sealers, AH Plus (DentSply Sirona, New York City, NY, USA) and BC (FKG, Le Crêt-du-Locle Switzerland) sealers to improve their antibacterial properties.MethodsDimethylaminohexadecyl Methacrylates (DMAHDM) were synthesized and incorporated into AH Plus and BC sealers at 5 weight percent (wt.%). The physical properties were assessed via film thickness, flow, contact angle, and solubility. The antibacterial properties were assessed by determining the number of colony-forming units (CFUs) of Enterococcus faecalis and scanning electron microscopy (SEM). Two-way ANOVA and Tukey tests were used to analyze the data.ResultsIncorporating DMAHDM at 5 wt.% increased the film thickness and reduced the flow of the AH Plus and BC sealers (P < 0.05), but the values were within clinically acceptable limits. Simultaneously, DMAHDM incorporation increased the contact angle of the sealers (P < 0.001). DMAHDM incorporation significantly (P < 0.001) inhibited the E. faecalis biofilms and resulted in complete eradication. In contrast, the AH Plus and BC control sealers had approximately 105 and 104 CFUs of bacteria, respectively. The SEM images revealed no E. faecalis colonies over the AH Plus sealers containing 5 wt.% DMAHDM, while the AH Plus control sealers were covered with a thick layer of biofilms.ConclusionsThe results of this study suggest that DMAHDM, as a contact-killing agent, could be used as an approach to prevent endodontic reinfections.Clinical RelevanceIntegrating DMAHDM into commercial sealers may enhance their antibacterial properties. These findings indicate a need for further investigation using more clinically relevant models to validate this approach.